Quantifying the Direct and Indirect Effects of Dissolved Organic Matter (DOM) on Aquatic Organisms: Interaction with pH and Quality Measures - Al-Reasi, Hassan A. (My University, 2012)
Dissolved organic matter (DOM) in natural waters is a heterogeneous mixture of organic molecules with direct and indirect influences on aquatic organisms. Although the influences are usually attributed to DOM quantity (quantified as Dissolved Organic Carbon, DOC), the role of quality (optical and binding characteristics obtained by absorbance and fluorescence spectroscopy and potentiometric titration, respectively) is not well-understood. Through an initial critical review of the literature, followed by experimental geochemical, toxicological, and physiological investigations, a number of conclusions were reached that improve our knowledge in this area. Freshwater DOM sources exhibit source-dependent protection against metal toxicity, in particular copper (Cu). Generally, for this indirect effect, optically-dark terrestrially-derived or allochthonous DOMs offer better protection than microbially-derived or autochthonous sources. Linear regressions revealed that the better ameliorative effect is principally related to a higher aromatic composition (specific absorption coefficient, SAC340) and a greater humic-like fluorescent component as quantified by parallel factor analysis (PARAFAC). In addition, the allochthonous DOMs were shown to have relatively higher magnitudes of titration index (TI), a new summary of chemical reactivity of DOM molecules obtained by titration analysis, and closely related to optical properties. TI was strongly correlated with SAC340, suggesting greater binding capacities for DOM molecules with higher SAC340. Consequently, a method for incorporation of SAC340 as a DOM quality measure into the Biotic Ligand Model (BLM) was developed which improved Cu toxicity predictions in experimental tests with natural DOMs. For direct effects, two basic physiological functions (Na+ metabolism and nitrogen excretion) of the adult water flea (Daphnia magna, a cladoceran crustacean) and the zebrafish (Danio rerio, a teleost fish) were investigated at circumneutral and acidic pH (≥ 7 and ~ 5, respectively). Three previously characterized, chemically-distinct natural DOM sources as well as a commercial humic acid (AHA) were examined. Regardless of the pH conditions, while Na+ regulation of D. magna remained unaffected by the presence of all DOMs, the passive diffusive efflux of Na+ in zebrafish was attenuated, indicating ameliorative action against unidirectional Na+ loss. In addition, only a distinct allochthonous-autochthonous DOM source stimulated the Na+ uptake rate of zebrafish at low pH. Ammonia excretion rates of D. magna were reduced at circumneutral pH by the most highly coloured, allochthonous DOM, and at low pH by all three natural DOMs. Both in D. magna and in D. rerio, urea excretion rates at both pH conditions were not influenced by the presence of the various DOMs, and the same was true for ammonia excretion in the zebrafish. A commercially prepared humic acid (Aldrich humic acid, AHA) exerted anomalous actions relative to those of natural DOMs, and does not appear to be representative of their normal effects. In contrast to the actions of DOM in detoxifying metals, these direct effects of DOMs on freshwater organisms appeared highly unpredictable with variable dependencies on the source, pH and species. This thesis has advanced our understanding of the relationships between DOM quality and its indirect and direct effects on aquatic organisms, and points to new directions for future work.
Keywords: Dissolved organic matter (DOM); Daphnia magna; Zebrafish; Biotic Ligand Model (BLM); Sodium metabolism; Ammonia and urea excretion; Biology; Pharmacology, Toxicology and Environmental Health; Physiology; Biology